O não-lugar dos professores nos entrelugares de formação continuada - Janete Magalhães Carvalho (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2005)
This article analyses the systems of representation of teachers, elected to participate as delegates in the Working Group on Teacher Formation and Valorisation during the Seminar on Educational Policy held in the State of Espírito Santo, to discuss the processes of continuing formation developed by the State Secretariat of Education. It uses in its analytical framework the the position held by the media in the general economy of symbolic goods, we start from the hypothesis according to which the educational practices of teachers and other social agents are shaped by a given social construction of reality, that is, by principles and views of education imposed, generally in a subtle fashion, by journalists and the general social space.